2013
DOI: 10.1007/s10753-013-9782-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of IL-15 and Natural Killer Cells on Osteoclasts and Osteoblasts in a Mouse Coculture

Abstract: This study analyzes the effect of interleukin-15 (IL-15) on osteoclast formation using a coculture of mouse osteoblasts and bone marrow cells (BMCs) stimulated with prostaglandin E2 (PGE2), which both have important role in rheumatoid arthritis (RA) and periodontal disease (PD). BMCs isolate lacking T (BM(T-)) or NK (BM(NK-)) cells, BMCs with no cells removed (BM(T+NK+)), purified NK cells, and purified T cells were each cocultured with osteoblasts in the presence or absence of PGE2 and/or IL-15. The number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 40 publications
3
42
0
1
Order By: Relevance
“…B ), we refer to them as effector memory T cells (T EM ). IL‐15 has also been shown to directly regulate osteoclasts and osteoblasts, either alone or in combination with RANKL . Together with the CTX time course (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…B ), we refer to them as effector memory T cells (T EM ). IL‐15 has also been shown to directly regulate osteoclasts and osteoblasts, either alone or in combination with RANKL . Together with the CTX time course (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…In human, IL‐15 was shown to drive osteoclast formation from monocyte precursors, but only in the presence of RA synovial NK cells, which up‐regulate both M‐CSF and membrane RANKL in response to IL‐15 . Moreover, a recent study showed that IL‐15 stimulates osteoblast apoptosis in mouse bone marrow cell cultures via activation of NK cells, again suggesting that IL‐15 is an inflammatory bone destructive factor . In fact, we are not aware of any reports indicating that IL‐15 may also display anti‐osteoclastogenic effects in vitro , and as targeting IL‐15R in vivo reduces disease progression and bone erosion in a mouse model of human RA, it is reasonable to conclude that the main role for IL‐15 on bone is to favour enhanced erosion.…”
Section: Discussionmentioning
confidence: 96%
“…39 In addition, IL-15 stimulates apoptosis of osteoblasts via activation of NK cells by Caspase3. 40 Strikingly, in the report, we first proved that GLP2 exerts its effect in part through the upregulation of iNOS expression. Our present approaches provided an unequirocal evidence for critical suppressor roles of the GLP2 in the osteoclasgenesis and supported the notion that GLP2 may be an alternative bona fide inhibiting factor of osteoporosis.…”
Section: Discussionmentioning
confidence: 92%